Prevalence of Toxocara vitulorum in Buffalo Calves in and around Mhow (Indore), Madhya Pradesh state of India - Parihar, Navneet; Bagherwal, Rajendra K.; Mehta, Hemant K.; Choudhary, Nidhi S.; Agrawal, Vivek; Gautam, Kuldeep; Sahu, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was performed from October 2019 to March 2020 to determine the distribution of Toxocara vitulorum in buffalo calves irrespective of age and sex in and around Mhow, District Indore, Madhya Pradesh. For this purpose, 200 fecal samples were collected from the rectum or freshly passed stool and were subjected to further parasitological investigation by flotation technique and Egg per gram (EPG) by McMaster technique. Out of 200 samples, 45 samples were positive for the T. vitulorum infection, having an overall 22.5% prevalence. Age-wise, 78% prevalence was observed in 0-6 months of age followed by 22% in 6-12 months age group, sex-wise prevalence in female calves was higher (27%) than male calves (18%) whereas month-wise highest prevalence 25.7% was observed in the month of November followed by 23.3% in the month of February, 22.8% each in October and January, and 20% each in December and March respectively.